2018
DOI: 10.1002/cam4.1907
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care initiation in pediatric oncology patients: A systematic review

Abstract: Palliative care (PC) aims to improve quality of life for patients and their families. The World Health Organization and American Academy of Pediatrics recommend that PC starts at diagnosis for children with cancer. This systematic review describes studies that reported PC timing in the pediatric oncology population. The following databases were searched: PubMed, Web of Science, CINAHL, and PsycInfo databases. Studies that reported time of PC initiation were independently screened and reviewed by 2 researchers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 65 publications
1
53
0
Order By: Relevance
“…But in fact, many clinicians do not have enough understanding about the importance and the roles of early palliative care initiations on children with chronic or life-threatening illnesses. 27,28 Moreover, clinicians working on facilities with hospitalization services only have limited time to dive in the communities. Hospitals are not fit for managing patients' and their families' psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
“…But in fact, many clinicians do not have enough understanding about the importance and the roles of early palliative care initiations on children with chronic or life-threatening illnesses. 27,28 Moreover, clinicians working on facilities with hospitalization services only have limited time to dive in the communities. Hospitals are not fit for managing patients' and their families' psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
“…17,[21][22][23][24][25] For children with cancer, referral to palliative care also often occurs late in the trajectory of illness, sometimes only days before death. 26,27 Recent systematic reviews suggest that access to specialist palliative care services is associated with improvements in quality of life, symptom control, perceived support, reduced time in hospital, less invasive treatment and greater advance care planning. 19,28,29 However, these reviews have aggregated the results for children and young people across conditions, and the evidence for those with cancer remains unclear because of conflicting results between individual studies 28 and the lack of work exploring condition-specific factors that may influence access to and benefit from specialist palliative care services.…”
Section: Introductionmentioning
confidence: 99%
“…With calls for greater adoption, it is of clinical importance to estimate the current population‐level provision and resource utilization of PC. A recent systematic review found studies conducted to date have been primarily single‐institution retrospective studies, with limited generalizability due to the small size of single‐institution cohorts and grouping across multiple malignancy types …”
Section: Introductionmentioning
confidence: 99%